Evolution of surface chemistry and morphology of hyperbranched polysiloxane polyimides in simulated atomic oxygen environment. (September 2015) - Lei, Xingfeng; Qiao, Mingtao; Tian, Lidong; Chen, Yanhui; Zhang, Qiuyu
Graphical abstract: Upon AO exposure, pristine polyimide is severely eroded and exhibits linear degradation behavior, while HBPSi polyimides demonstrate high AO survivability. Highlights: Hyperbranched polysiloxane polyimides (HBPSi PIs) were fabricated by co-polymerizing HBPSi with imide monomers. The degradation behavior of HBPSi PIs is assessed based on its evolution of surface chemistry and morphology. There is a percolation threshold of HBPSi addition to achieve the most desirable atomic oxygen (AO) resistance. Desirable AO resistance is associated with the rapid formation of a much denser and more connected silica passivating layer. The silica passivating layer formed in situ is time-dependent and grows with AO fluence. Abstract: Hyperbranched polysiloxane (HBPSi) polyimide membranes were fabricated by copolymerizing amine-functionalized HBPSi and imide monomers. The atomic oxygen (AO) resistance of the resulting polyimides were investigated in simulated AO environment, based on their evolution of surface chemistry and morphology. Results indicated that a silica passivating layer finally formed on the membrane surfaces and, there was a percolation threshold of HBPSi addition to achieve the most desirable AO resistance. This is explained by the formation of a much denser and more connected silica passivating layer in shorter time on the membrane surface at high HBPSi loading upon AO exposure.